Effects of naturally smoked sugar and frozen storage time on aerobically packaged bacon using a conventional and natural curing systems - Hobson, Allison Whitney (Kansas State University, 2018)
Two studies were conducted to determine the effectiveness of naturally smoked sugar in a conventional and natural curing brines to inhibit lipid oxidation in frozen, aerobically packaged, layout style bacon. Commercial pork bellies were trimmed and cut in half creating anterior and posterior sections. Each section was randomly assigned to one of two treatments targeted 12% injection: control brine or a brine containing naturally smoked sugar (n =15/treatment). In the first study a conventional control brine consisted of 76.4% water, 11.8% salt, 8.00% sugar, 1.70% sodium phosphate, 1.60% sodium nitrite, and 0.450% sodium erythorbate. The treatment brine contained the same ingredients with the addition of 5.00% naturally smoked sugar. In the second study a natural control curing brine was utilized and contained 72.0% water, 13.4% sea salt, 8.00% cane sugar, and 6.67% celery juice. While treatment brine had the same ingredients as the natural control brine with the addition 5.00% smoked sugar. Bacon slices were randomly assigned to four sensory and GCMS frozen storage periods (0, 40, 80, and 120 day) or seven thiobarbituric acid reactive substances (TBARS) frozen storage times (0, 20, 40, 60, 80, 100, and 120 day). To measure lipid oxidation trained sensory evaluation, TBARS, and gas chromatography mass spectrometry (GCMS) was conducted after the assigned frozen storage periods. All bacon slices were stored aerobically at -18 ± 2 °C for their designated storage period. The first study panelist scores for oxidized flavor of the conventional control bacon increased from day 0 to 120; whereas the naturally smoked sugar treatment had decreased panelist scores (P > 0.16) for oxidized flavor intensity compared to the control bacon. Also, TBARS results values for the conventional control bacon increased (P < 0.01) from day 20 to day 120; while the conventional naturally smoked sugar treatment remained constant (P > 0.99). Hexanal content for conventional control increased (P < 0.003) during frozen storage; but naturally smoked sugar TBARS values were not different from day 0 of storage (P > 0.734). Concentration of heptanal in conventional control bacon was the highest (P < 0.003) at day 80 and 120 of frozen storage. Heptanal content in conventional bacon with naturally smoked sugar was not different from day 0 of frozen storage (P > 0.846). Conventional bacon formulated with naturally smoked sugar had greater concentrations of creosol and syringol than control bacon (P < 0.003). In the second study, naturally cured bacon had increased panelist scores for oxidized flavor from day 0 to 120 of frozen storage (P < 0.001). Natural bacon with smoked sugar had oxidized flavor scores that remained constant during frozen storage (P > 0.936). Naturally cured bacon displayed increased TBARS values from day 20 to 120 of frozen storage (P < 0.001). Naturally cured bacon with smoked sugar exhibited static TBARS values throughout the frozen storage period (P > 0.196). Thus, smoked sugar is an effective antioxidant in frozen sliced, aerobically packaged, conventionally cured and naturally cured bacon.
Keywords: Frozen storage; Bacon; Lipid oxidation; Naturally smoked sugar; Sensory